Post-Minkowskian solution for the small-deflection motion of test particles in Kerr–Newman spacetime. (2nd April 2019) - Yang, Bo; Jiang, Chunhua; Lin, Wenbin
Abstract: We derive the second-order post-Minkowskian solution for the small-deflection motion of test particles in the external field of the Kerr–Newman black hole via an iterative method. The analytical results are exhibited in the coordinate system constituted by the particles' initial velocity unit vector, impact vector, and their cross-product. The achieved formulas explicitly give the dependences of the particles' trajectory and velocity on the time once their initial position and velocity are specified, and can be applied not only to a massive particle, but also to a photon as well.